HYDROTHERMAL GAS EQUILIBRIA: THE H2O-H2-CO2-CO-CH4 SYSTEM - EVIDENCES OF MAGMATIC AND CRUSTAL CONTRIBUTION - Chiodini G.; Marini L. (My University, 1998)
The difficulty in measuring reservoir gas concentrations in geothermal systems often forces the use of gas ratios in a separated vapor phase to investigate reservoir conditions.Measured CO/CO2 and H2/H2O ratios of fumarolic fluids and vapors from geothermal wells representative of twenty-two different hydrothermal systems are consistent with theoretical values obtained from either of two commonly used redox buffers, indicating that CO and H2 attain chemical equilibrium in the hydrothermal reservoir. Use of different fO2-buffers has little effect on these functions. Many measured CH4/CO2 ratios are, instead, inconsistent with theoretical values obtained with any redox buffer. Since CH4/CO2 ratios are strongly affected by redox conditions in the gas equilibration zone, this disagreement between measured and theoretical values likely indicates that either no unique fO2-buffer is active in all the hydrothermal environments or that CH4 is not in equilibrium with the other gases.The weight of CH4 on the 3log(XCO/XCO2) + log(XCO/XCH4) function is relatively small. Therefore this function and the log(XCO/XCO2) - log(XH2/XH2O) function, both of which are independent upon redox conditions, were used. These functions gave reasonable estimates of the equilibrium temperature and either the fraction of separated steam or the fraction of condensed steam in each sample. From these data, the CO/CO2, H2/H2O, and H2/CO ratios in the hypothetical single saturated vapor phase were calculated and used to investigate fO2 and fCO2 distributions in the considered twenty-two hydrothermal systems. Recalculated fCO2 values are generally consistent, within one-half log-unit, with the full equilibrium function of Giggenbach (1984), Giggenbach (1988) although production of thermometamorphic CO2 might locally take place. It is evident that no unique fO2-buffer is active in all the hydrothermal environments. This fact imply that CH4 could have attained chemical equilibrium with other gas species in the H2O-H2-CO2-CO-CH4 system.